Apreciaciones sobre la quinta disciplina en la construcción de organizaciones educativas inteligentes - Furguerle Rangel, Johel; Pacheco Barrios, José; Bastidas Pacheco, Gilberto (Universidad de Costa Rica, 2018)
In the educational institutions, the organizational aspects have been relegated because the educational policy has been careful to produce new curricular projects trapped in archaic organizational frameworks, with the consequent impossibility for the achievement of the institutional objectives. Under this consideration, in this article, the attitudes that teachers have towards intelligent organizations based on Serge’s fifth discipline, which expresses the construction of systems thinking, were evaluated. A sample of 40 teachers from the high school Bolivariano "Dr. Burelli Rivas "located in the municipality of Valera, Trujillo state, Venezuela. The investigation was field, transversal, descriptive type. The survey was used to collect data and as an instrument two self-administered Likert-type questionnaires were applied, after obtaining informed consent. Teacher appreciation was high in terms of personal mastery, mental models, and systemic thinking, and was media, with respect to all aspects that define intelligent organizations. It is concluded that the teachers surveyed have a positive attitude towards the systemic thinking of the fifth discipline, since it is the integrator of the other doctrines or postulates. However, teachers believe that the practice of shared vision is fairly important, that is, the genuine belief of a common future, for the achievement of the objectives of educational institutions.